Merak Port Customer Loyalty - Sohwa Rizkia Rizal; Agung Kresnamurti Rivai; Rahmi Rahmi (Universitas Negeri Gorontalo, 2022)
The aim of this research was to examine the direct impact of service quality, trust and customer satisfaction variables on customer loyalty. As well as the indirect effect between service quality and customer satisfaction on customer loyalty through trust variable. This research uses a quantitative approach and data collected using survey with questionnaire as an instrument. The sample of this research are 200 Merak Port customers, that have visited Merak Port at least two times in the past year and have visited Merak Port before and after 2019. The data analysis technique uses SPSS version 22 LISREL 8.8 to analyze and process research data. The hypothesis finding show that only the customer satisfaction variable positively and significantly affect customer loyalty. The trust variable as a mediator in the relationship between service quality and customer satisfaction on customer loyalty shows insignificant results.